Taking class struggle as the key, counter-attack the rightist wind to overturn verdicts: selected fine-arts big-character posters by the workers of Yangquan (以阶级斗争为纲，回击右倾翻案风) - Yangquan workers’ amateur arts group (People's Fine Arts Press, 1976)
This poster is part of the campaign against Deng Xiaoping (as yet unnamed) in the spring of 1976. Created by the Yangquan workers’ amateur arts group, comprising amateur artists from agricultural machinery, mining, steel, and railroad industries, and from fine arts and propaganda divisions of workers’ cultural palaces in Yangquan. Yangquan, in Shanxi Province, is an industrial centre that nurtures amateur artists, and was active in the Cultural Revolution.